Comparison of Pregnancy Outcome between 4 and 6 cm Cervical os Dilatation to Demarcate Active Phase of Labour: A Cross-Sectional Study - Nadzirah Mohd Fathil; Rahana Abd Rahman; Azmawati Mohd Nawi; Ixora Kamisan Atan; Aida Hani Kalok; Nor Azlin Mohamed Ismail; Zaleha Abdullah Mahdy; Farin Masra; Zuhailah Muhammad; Shuhaila Ahmad (Journal of Pregnancy)
This is a cross-sectional study comparing pregnancy outcomes between participants with 4 and 6 cm of cervical os dilatation at the diagnosis of the active phase of labour. It was conducted in a single tertiary centre involving low-risk singleton pregnancies at or beyond 37 weeks with spontaneous onset of labour. A total of 155 participants were recruited, 101 in group 1 (4 cm) and 54 in group 2 (6 cm). Both groups were similar in mean maternal age, mean gestational age at delivery, ethnicity, median haemoglobin level at delivery, body mass index, and parity. There were significantly more participants in group 1 who needed oxytocin augmentation (p<0.001) for the longer mean duration (p=0.015), use of analgesia (p<0.001), and caesarean section rate (p=0.002). None of the women had a postpartum haemorrhage or a third- or fourth-degree perineal tear, and none of the neonates required admission to the neonatal intensive care unit. There were significantly more nulliparas who had a caesarean section as compared to multiparas. A cervical os dilatation of 6 cm reduces the risk of caesarean section by 11% (95% CI, 0.01-0.9) and increases three times more the need for analgesia (AOR=3.44, 95% CI, 1.2-9.4). In conclusion, the demarcation of the active phase of labour at a cervical os dilatation of 6 cm is feasible without an increase in maternal or neonatal complications.